Program "note your money worth": an assessment of its effects on the collection of vat in retail trade cearense - Nathalia Fontenele Silva (2012)
This paper analyzes the impact of the Program âYour Receipt is Worth Moneyâ created by the Department of Finance of the state of CearÃ, to stimulate people to demand receipts when purchasing goods from stores. Thus, the Program tends to increase the collecting of VAT due to the issuing of invoices and, at the same time, lower tax evasion, since at SEFAZ/CE, part of the collection returns to the tax payer registered in the program. The analysis of the effects of the Program âYour Receipt is Worth Moneyâ SEFAZ/CE, on the collection of the State of CearÃ, was performed using linear regression models, and, for this, we used the collection of VAT retail trade, the indices of the volume of retail sales and industrial production. In all models, these ratios were statistically significant and positively affect the collection of VAT retail. In terms of evaluation, it was observed that, in some models, the Program âYour Receipt is Worth Moneyâ has a positive effect on the collection and in others the effect is null-statistically equal to zero.